Accurate Reconstruction of Mandibular Defects With Vascularized Bone Flaps Through Utilization of Mandible Space-Retention Guides. Issue 5 (27th July 2022) - Wang, Chengyi; Meng, Zhaoqiang; Jie, Bimeng; Li, Ruiliu; He, Yang; Xu, Mingming
Abstract : Purpose: Comprehensive evaluation of the effects of using computer-aided design and space retention guide technology to reconstruct mandibular defects using vascularized autogenous bone flaps. Method: This study included 8 patients who received autogenous bone flaps (2 cases of vascularized fibula flaps and 6 cases of vascularized iliac flaps) for mandibular defect reconstruction at Peking University School and Hospital of Stomatology, from July 2018 to May 2021. All patients received digital surgery planning, computer aided design/computer aided manufacture, surgical guide technique for the removal of diseased bone segments, as well as vascularized fibular flap/iliac flap reconstruction. Three-dimensional deviations were analyzed after the operation. Result: The mandibular defects of all 8 patients were successfully reconstructed using the vascularized fibular flap/iliac bone flap. There were no serious complications at either the donor site or recipient site during our follow-up. The average three-dimensional deviation of all 8 patients was 1.92 mm, based on comparisons of preoperative design and actual postoperative computed tomography. Conclusion: Utilizing computer aided design/computer aided manufacture, we designed a new mandibular space-retention guide, which can accurately translate the preoperative digital design plan to real-time surgery with satisfactory accuracy and efficacy.